Permohonan Pernyataan Pailit Terhadap Perusahaan Modal Ventura Yang Tidak Memiliki Izin - Hendri Sita Ambar K; Bianca Belladina (ADHAPER: Jurnal Hukum Acara Perdata, 2020)
One of many cases in point of controversial bankruptcy was the case of bankruptcy statement and debt rescheduling of PT Brent Ventura (BV). Overall, nine applications submitted against this company have been rejected by the judges of the commercial court, it made certain assumptions that PT BV was immune from the debt rescheduling process and bankruptcy as in Decision of Commercial Court Number 50/Pdt.Sus.Pailit/2014/PN.Niaga.Jkt. Pst. The inaccuracy of the consideration of the decision became the core analysis in this normative research using case studies and conceptual approach. To summarize, the analysis result of Decision of Commercial Court Number 50/Pdt. Sus. Pailit/2014/PN.Niaga.Jkt.Pst that there were some inaccuracies in the legal considerations of the court decision. The judges considered that PT BV was a venture capital company under the supervision of the Otoritas Jasa Keuangan (OJK) and the bankruptcy petition could only be ﬁ led by the OJK. In conclusion, the consideration of the judges was inaccurate due to such restrictions only applied to debtors whose business activities related to public interest, which was MTN publishing was not included in the scope of activities. Hence, petition of bankruptcy statement to PT BV could be ﬁled by individual or legal entities other than OJK.